2015
DOI: 10.1016/j.pscychresns.2015.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in abnormal white matter development associated with conduct disorder in children

Abstract: Associations between white matter pathway abnormalities and antisocial personality disorder in adults are well replicated, and there is some evidence for an association of white matter abnormalities with conduct disorder (CD) in adolescents. In this study, white matter maturation using diffusion tensor imaging (DTI) was examined in 110 children aged 10.0 ± 0.8 years selected to vary widely in their numbers of CD symptoms. The results replicated age-related increases in fractional anisotropy (FA) found in previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 56 publications
3
26
0
Order By: Relevance
“…Notably, some studies of children and adolescents with a broad range of disorders including ADHD, CD, alcohol use disorder, and OCD have also shown a trend similar to the present results with increased white matter integrity in patient populations in the CC, although these results were observed in the context of specific case-control type designs rather than reflecting transdiagnostic characteristics (De Bellis et al, 2008;Decety et al, 2015;Jayarajan et al, 2012;Lawrence et al, 2013;Menks et al, 2017;Pape et al, 2015;Zarei et al, 2011;Zhang et al, 2014). It is notable that in the context of such studies it has been hypothesized that individuals with psychopathology may have an accelerated trajectory of white matter development with an earlier peak and subsequent earlier and steeper decline, thus explaining increased integrity relative to controls during childhood but decreased integrity during adulthood (Menks et al, 2017).…”
Section: General Factor Correlatessupporting
confidence: 87%
“…Notably, some studies of children and adolescents with a broad range of disorders including ADHD, CD, alcohol use disorder, and OCD have also shown a trend similar to the present results with increased white matter integrity in patient populations in the CC, although these results were observed in the context of specific case-control type designs rather than reflecting transdiagnostic characteristics (De Bellis et al, 2008;Decety et al, 2015;Jayarajan et al, 2012;Lawrence et al, 2013;Menks et al, 2017;Pape et al, 2015;Zarei et al, 2011;Zhang et al, 2014). It is notable that in the context of such studies it has been hypothesized that individuals with psychopathology may have an accelerated trajectory of white matter development with an earlier peak and subsequent earlier and steeper decline, thus explaining increased integrity relative to controls during childhood but decreased integrity during adulthood (Menks et al, 2017).…”
Section: General Factor Correlatessupporting
confidence: 87%
“…To date, however, most studies on CD have focused only on male youths 9,10,13,19 or female youths alone. 11 Three studies 12,14,20 have included mixed-sex samples but were underpowered to test for sex-by-diagnosis interactions, thereby contributing to the inconsistencies in the literature. These data highlight the need to investigate similarities across the sexes as well as testing for potential sex-specific effects.…”
mentioning
confidence: 99%
“…Our third aim was to examine the impact of callousunemotional (CU) traits (ie, reduced empathy and guilt, combined with shallow emotions and the callous use of others; see the "limited prosocial emotions" specifier for CD in DSM-5 1 ) on WM alterations associated with CD. Indeed, several studies 14,20 have failed to account for heterogeneity within CD in relation to CU traits, which might have contributed to inconsistent findings across studies. Two recent studies showed that CU traits influenced the pattern of WM differences in youths with CD.…”
mentioning
confidence: 99%
“…Similar discrepancies exist when following-up on the relationship of specific DTI tensors in relation to behavioral severity of conduct disorder, such as psychopathic traits, callous unemotional traits, and amount of conduct disorder symptoms 31,32,[35][36][37] . Some identify positive correlations 35,37 , while others reported negative 31,32 or no correlations at all 29 . These inconsistent findings regarding the direction and location of white mater alterations may result from differences in the analysis approaches used (e.g.…”
Section: Altered White Matter Structures In Conduct Disordermentioning
confidence: 82%
“…Another study investigating pre-adolescents with conduct problems indicated no sex differences for fractional anisotropy, but did observe a stronger relationship between conduct disorder symptoms and altered white matter integrity (i.e. axial diffusivity) in several tracts, for example the uncinate fasciculus in girls in comparison to boys 35 . Since the uncinate fasciculus interconnects the orbitofrontal cortex and amygdala, this major white matter tract has often been associated with antisocial behavior 9,16,17 .…”
Section: Sex Differences and Conduct Disordermentioning
confidence: 94%